Supply Chain Design of Potato Commodity in Wonosobo Regency, Central Java - Indonesia - Sarjono, Haryadi; Sanny, Lim; Melati, Ina; ., . (International Journal of Engineering and Technology, 2018)
Today, the demand for horticultural commodities is relatively high, making these commodities more important in the growing Indonesian economy. One of the horticultural commodities is the potato (Solanum tuberosum). Potatoes are widely used as ingredients in the light meal industry such as potato chips. Restaurants and fast food industry also use potatoes as the ingredients. Wonosobo regency is one of the areas in Java producing a lot of potatoes and the majority of the population work as farmers. The purpose of this research is to find out the network design of potato supply chain in Wonosobo regency in order to design a more effective and efficient one. This research uses the descriptive qualitative method and the processes of collecting data are observation, interview, and documentation. The results suggest that the current supply chain design of potatoes is from farmers, middlemen, retailers, and consumers. An alternative network design proposed is the farmers should channel the lower quality potatoes directly to the retailers. While another alternative is, for the good quality potatoes, the farmers should sell them to cooperative for export.Â Â